1-Benzoyl-3-(4-chlorophenyl)thiourea dichloromethane hemisolvate - Selvakumaran, N. (International Union of Crystallography, 2012)
In the title hemisolvate, C(14)H(11)ClN(2)OS·0.5CH(2)Cl(2), an anti disposition is found for the thione and ketone atoms, as well as the N—H H atoms; the dichloromethane C atom lies on a twofold axis. The central chromophore (including the two adjacent ipso C atoms) is planar (r.m.s. deviation = 0.021 Å) owing to the presence of an intramolecular N—H⋯O hydrogen bond, which closes an S(6) loop. Significant twists are evident in the molecule, the dihedral angles between the central moiety and the phenyl and benzene rings being 29.52 (7) and 40.02 (7)°, respectively. In the crystal, eight-membered {⋯HNC= S}(2) synthons with twofold symmetry form via N—H⋯S hydrogen bonds. The dimers are connected into a supramolecular chain along [111] by C—H⋯O interactions. The chains stack along the c axis, forming columns which define channels in which the occluded dichloromethane molecules reside.